2018
DOI: 10.1002/alr.22218
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency in interleukin‐10 production by M2 macrophages in eosinophilic chronic rhinosinusitis with nasal polyps

Abstract: Background: M2 macrophages are characterized by high interleukin-10 (IL-10) expression and are critical for resolving inflammation. Although increased accumulation of M2 macrophages has been demonstrated in chronic rhinosinusitis with nasal polyps (CRSwNP), particularly the eosinophilic type, their functional relevance in CRSwNP remains poorly understood.Methods: M1 and M2 macrophages and IL-10 expression in sinonasal tissues were detected by doubleimmunofluorescence staining. THP-1 cells, a human monocytic le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 44 publications
(121 reference statements)
6
18
0
Order By: Relevance
“…In contrast to the finding in eosinophilic nasal polyps, we did not detect CCL24 expression in macrophages in non‐eosinophilic polyps. Our previous studies demonstrated a predominant M2 phenotype of macrophages in eosinophilic nasal polyps and skewed M1 phenotype of macrophages in non‐eosinophilic nasal polyps . In the present study, we found the macrophages in both eosinophilic and non‐eosinophilic polyps exhibited expression of NK1R.…”
Section: Discussionsupporting
confidence: 70%
“…In contrast to the finding in eosinophilic nasal polyps, we did not detect CCL24 expression in macrophages in non‐eosinophilic polyps. Our previous studies demonstrated a predominant M2 phenotype of macrophages in eosinophilic nasal polyps and skewed M1 phenotype of macrophages in non‐eosinophilic nasal polyps . In the present study, we found the macrophages in both eosinophilic and non‐eosinophilic polyps exhibited expression of NK1R.…”
Section: Discussionsupporting
confidence: 70%
“…A histological study on a large sample of CRS tissues demonstrated that CRSwNP presented a higher amount of immune cell infiltration compared with CRSsNP, and there were higher levels of cell infiltration of cytotoxic CD8 + T cells, B cells and macrophages in CRSwNP, as determined by immunohistochemistry (14). In addition, ECRSwNP has been reported to be associated with fewer M1 macrophages and more M2 macrophages compared with non-ECRSwNP, and the number of IL-10 + CD68 + macrophages was decreased in ECRSwNP (15). Specific chemokines and cytokines, such as MIP-1α, IL-5 and RANTES, are crucial to eosinophil recruitment, survival and differentiation (16)(17)(18).…”
Section: Introductionmentioning
confidence: 97%
“…This suggests no difference in the number of differentiated M1 and M2 macrophage cells between the two groups. Then, we measured the mRNA expression levels of CCR7 and IL-10 as markers for M1 and M2 macrophages, respectively (41,42). The mRNA expression level of CCR7 was higher in M1 than in M2 macrophages (U = 27, p = 0.0079), whereas that of IL-10 was higher in M2 than in M1 macrophages (U = 0, p < 0.0001), thus con rming the differentiation into M1 and M2 macrophages (Suppl.…”
Section: Cytokine Expression In M1 and M2 Macrophages: Differences Bementioning
confidence: 99%